Light-controlled flavonoid biosynthesis in fruits - Zoratti, Laura; Karppinen, Katja; Luengo Escobar, Ana; Häggman, Hely; Jaakola, Laura (Frontiers in Plant Science, 2014)
Light is one of the most important environmental factors affecting flavonoid biosynthesis in plants. The absolute dependency of light to the plant development has driven evolvement of sophisticated mechanisms to sense and transduce multiple aspects of the light signal. Light effects can be categorized in photoperiod (duration), intensity (quantity), direction and quality (wavelength) including UV-light. Recently, new information has been achieved on the regulation of light-controlled flavonoid biosynthesis in fruits, in which flavonoids have a major contribution on quality. This review focuses on the effects of the different light conditions on the control of flavonoid biosynthesis in fruit producing plants. An overview of the currently known mechanisms of the light-controlled flavonoid accumulation is provided. R2R3 MYB transcription factors are known to regulate by differential expression the biosynthesis of distinct flavonoids in response to specific light wavelengths. Despite recent advances, many gaps remain to be understood in the mechanisms of the transduction pathway of light-controlled flavonoid biosynthesis. A better knowledge on these regulatory mechanisms is likely to be useful for breeding programs aiming to modify fruit flavonoid pattern.